From the history of Lithuanian pedagogy (K. Nezabitauskas’ primer “The New Reading…”) - Auryla, V.; Žukas, V. (Psichologija, 1962)
At the beginning of 19th century, in the age of the collapse of feudalism and formation of capitalist relations, enlightenment activity in Lithuania became more intense. The important role in this area was played by Vilnius University: the professors of this university studied the history of Lithuania, collected records, Lithuanian students paid much attention to language matters, literary studies and enlightenment of the Lithuanian nation. One of the most prominent activists of Lithuanian publishing was K. Nezabitauskas (1800 – 1876). In 1824 his primer “The New Reading for Small Children” was published. Following the new basics of pedagogy, the primer contained readings with text illustrations which were a novelty, and Lithuanian proverbs and bibliography list of Lithuanian publications. K. Nezabitauskas sought to attract children’s attention and make learning an easy and vivid occupation. In the introduction to the primer, he spoke against scholastic learning. In his primer K. Nezabitauskas provided practical guidance and popular scientific information. The short articles included in the primer can be considered the first manifestations of the Lithuanian secular literature for children. Proverbs and, especially the bibliography list, witness that the primer was also intended to further education of the readers, mostly the youth. This primer was appraised by its contemporary Lithuanian writer D. Poška, Russian scientist P. Kepen, active culture character L. Rogalskis, Polish newspaper “Kurjer Litewski“, etc. In the second half of 19th century, M. Akelaitis intended to republish it; he was planning to skip the religious part and include folklore songs (the handwriting of this work has preserved). Though this primer by K. Nezabitauskas had certain ideological setbacks, its historical value is still very significant. K. Nezabitauskas was the first who started writing secular reading texts to Lithuanian children, who directed children’s education in a practical direction and utilized new principles of book compilation.